Therapeutic intervention with anti-TNF alleviates colonic and hepatic toxicity induced by perfluorooctanoic acid (PFOA)Mendeley Data - Wei Li; Yongjing Qian; Xiaojing Cai; Yu He; Xiannan Meng; Ling Zhang (Ecotoxicology and Environmental Safety)
Perfluorooctanoic acid (PFOA) is a prevalent and chemically stable environmental contaminant. Our preliminary data suggest that chronic exposure to PFOA induces colonic damage in mice that resembles inflammatory bowel disease (IBD). Anti-TNF therapies are commonly used in the clinical management of IBD. Building upon our previous findings, we administered anti-TNF treatment to mice exposed to PFOA. Our results show that anti-TNF therapy significantly reduces the colonic inflammatory response, activation of the NLR family pyrin domain containing 3 (NLRP) inflammasome, and apoptosis induced by PFOA. Additionally, anti-TNF treatment restores intestinal barrier integrity, which is disrupted by PFOA exposure, and enhances the regenerative capacity of the colon by promoting intestinal stem cell function. Furthermore, anti-TNF therapy effectively mitigates hepatic inflammation, liver dysfunction, lipid metabolism disturbances, NLRP3 inflammasome activation, and apoptosis in the liver triggered by PFOA. In conclusion, our study provides compelling evidence that anti-TNF therapy can alleviate both colonic and hepatic injuries induced by PFOA exposure. This research expands our understanding of environmental toxin-induced diseases and offers potential therapeutic strategies for managing PFOA-related disorders in the future.